Self Control Pengendara Motor Pada Anak di Bawah Umur di Nagari Koto Baru Kecamatan Sungai Pagu Kabupaten Solok Selatan - Fitriani, Riri; Nasril, Nasril; Jemkhairil, Jemkhairil (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2024)
This research aims to describe the Self Control of motorbike riders among minors in Nagari Koto Baru, Sungai Pagu District, South Solok Regency. This research method is qualitative research. The type of qualitative research used in this research is descriptive qualitative. Data collection techniques through observation and interviews. The research subjects in this study were minors who drove motorized vehicles, aged 9-14 years and the elderly. Research subjects were determined using purposive sampling technique. Research findings show; 1) Self-control of behavior (Behavior Control). From the behavioral aspect of minors using motorized vehicles, not using helmets and using motorized vehicles by speeding, not using rear-view mirrors. 2) Cognitive Control (Cognitive Control) The impact of cognitive control of minors who use motorized vehicles, is seen in terms of how to assess relationships in an event. An example of this is using a motorized vehicle at high speed by using speeding skills along the highway. 3) Controlling decisions (Decisional Control), seen from making choices that will function well with opportunity and freedom. For example, carrying a motorbike at high speed so that it is out of control, riding three passengers, carrying a motorbike in a racing style.